0432 Characterizing Risky Sleep in the Military. (27th April 2018) - McDonald, J; Ganulin, M; LoPresti, M; Adler, A
Abstract: Introduction: Poor sleep is endemic in the US military. Soldiers frequently obtain less than the recommended amount of sleep. Furthermore, sleep disorders, such as insomnia, are prevalent in this population. The goal of this study was to assess differences in the sleep knowledge and sleep habits between soldiers characterized as "risky" or "non-risky" sleepers. Methods: Cross-sectional anonymous survey data from 2, 506 active-duty soldiers were analyzed, including the Insomnia Severity Index (ISI), the Patient Health Questionnaire (PHQ-9), sleep knowledge questions (e.g., awareness of how sleep impacts performance), sleep habits questions (e.g., making sure alcohol intake does not interfere with sleep), and daily sleep duration. Risky sleepers were operationalized as reporting: 1) <= 6 hours of sleep/day; and 2) moderate to severe insomnia symptoms. Chi-square tests and ANOVAs were used to analyze group differences between risky and non-risky sleepers. Results: Risky sleepers made up 22.0% of the sample, Officers had lower risky sleeper prevalence rates than enlisted personnel. Risky sleepers demonstrated significantly higher sleep knowledge on 5 out of 7 items than non-risky sleepers. They did not report significantly different healthy sleep habits, except for reporting more avoidance of caffeine use at least 6 hours before bed. Despite these findings, risky sleepers endorsed greater overall consumption of coffee and energy drinks. Risky sleepers were also more likely to report having made an appointment to talk with a medical professional about their sleep, and were more likely to report using prescription and over-the-counter sleep medications. Conclusion: Despite better sleep knowledge, risky sleepers engage in higher caffeine and sleep medication use as compared to non-risky sleepers. These results demonstrate the potential limits of sleep education as a mitigation factor in sleep management for risky sleepers. Alternative interventions for risky sleepers should be considered. Such interventions could include training leaders to encourage and prioritize healthy sleep in high risk occupational contexts. Future research should explore environmental and occupational factors that may mitigate potential for becoming a risky sleeper. Support (If Any): This study was funded as part of the US Army's Military Operational Medicine Research Program.